Znajomość języka angielskiego jako wartość w świetle wybranych materiałów do nauki tego języka z lat 1788-1947 - przyczynek do badań nad dyskursem edukacyjnym = Knowledge of English as a value in the light of selected materials for learning this language from 1788-1947 - a contribution to research on educational discourse - Kotlarska, Irmina (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The study presents the ways of conceptualizing English and its knowledge in selected materials for learning this language from the years 1788-1947.
Keywords: teksty do nauki języka angielskiego; konceptualizacja; dyskurs edukacyjny; aksjologizacja treści; texts for learning English; conceptualization; educational discourse; evaluation of content; 18-20 w.